An Overview of Sucrose Synthases in Plants - Stein, Ofer; Granot, David (Frontiers in Plant Science, 2019)
Sucrose is the end product of photosynthesis and the primary sugar transported in the phloem of most plants. Sucrose synthase (SuSy) is a glycosyl transferase enzyme that plays a key role in sugar metabolism, primarily in sink tissues. SuSy catalyzes the reversible cleavage of sucrose into fructose and either uridine diphosphate glucose (UDP-G) or adenosine diphosphate glucose (ADP-G). The products of sucrose cleavage by SuSy are available for many metabolic pathways, such as energy production, primary-metabolite production and the synthesis of complex carbohydrates. SuSy proteins are usually homotetramers with an average monomeric molecular weight of about 90 kD (about 800 amino acids long). Plant SuSy isozymes are mainly located in the cytosol and plasma membrane, but some SuSy proteins are found in the cell wall, vacuoles and mitochondria. Plant SUS gene families are usually small, containing between four to seven genes, with distinct exon-intron structures. Plant SUS genes are divided into three separate clades, which are present in both monocots and dicots. A comprehensive phylogenetic analysis indicates that a first SUS duplication event may have occurred before the divergence of the gymnosperms and angiosperms and a second duplication event probably occurred in a common angiosperm ancestor, leading to the existence of all three clades in both monocots and dicots. Plants with reduced SuSy activity have been shown to have reduced growth, reduced starch, cellulose or callose synthesis, reduced tolerance to anaerobic-stress conditions and altered shoot apical meristem function and leaf morphology. Plants overexpressing SUS have shown increased growth, increased xylem area and xylem cell-wall width, and increased cellulose and starch contents, making SUS high-potential candidate genes for the improvement of agricultural traits in crop plants. This review summarizes the current knowledge regarding plant SuSy, including newly discovered possible developmental roles for SuSy in meristem functioning that involve sugar and hormonal signaling.